Detection of prostate cancer‐specific transcripts in extracellular vesicles isolated from post‐DRE urine. Issue 9 (17th April 2017) - Pellegrini, Kathryn L.; Patil, Dattatraya; Douglas, Kristen J.S.; Lee, Grace; Wehrmeyer, Kathryn; Torlak, Mersiha; Clark, Jeremy; Cooper, Colin S.; Moreno, Carlos S.; Sanda, Martin G.
Abstract : Background : The measurement of gene expression in post‐digital rectal examination (DRE) urine specimens provides a non‐invasive method to determine a patient's risk of prostate cancer. Many currently available assays use whole urine or cell pellets for the analysis of prostate cancer‐associated genes, although the use of extracellular vesicles (EVs) has also recently been of interest. We investigated the expression of prostate‐, kidney‐, and bladder‐specific transcripts and known prostate cancer biomarkers in urine EVs. Methods : Cell pellets and EVs were recovered from post‐DRE urine specimens, with the total RNA yield and quality determined by Bioanalyzer. The levels of prostate, kidney, and bladder‐associated transcripts in EVs were assessed by TaqMan qPCR and targeted sequencing. Results : RNA was more consistently recovered from the urine EV specimens, with over 80% of the patients demonstrating higher RNA yields in the EV fraction as compared to urine cell pellets. The median EV RNA yield of 36.4 ng was significantly higher than the median urine cell pellet RNA yield of 4.8 ng. Analysis of the post‐DRE urine EVs indicated that prostate‐specific transcripts were more abundant than kidney‐ or bladder‐specific transcripts. Additionally, patients with prostate cancer had significantly higher levels of the prostate cancer‐associated genes PCA3 and ERG . Conclusions : Post‐DRE urine EVs are a viable source of prostate‐derived RNAs for biomarker discovery and prostate cancer status can be distinguished from analysis of these specimens. Continued analysis of urine EVs offers the potential discovery of novel biomarkers for pre‐biopsy prostate cancer detection.